THE RIGHTS OF THE LEGITIMATE CHILD OF AN APOSTATE WIFE ACCORDING TO ISLAMIC LAW - CahyoAnugroh Rachman; Fiska Silvia Raden Roro (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This research studies the rights of biological children due to apostate wives in the perspective of Islamic inheritance law. The purpose of this study is to analyze the legal consequences of couples who convert to Islam in the perspective of Islamic law and analyze the distribution and status of Islamic inheritance to children if their parents commit apostasy in various marital conditions associated with Islamic inheritance law.Normative juridical researchis applied as the method of the research. It can be concluded that the legal consequences of a couple who converted to Islam in the perspective of Islamic law is that the marriage is broken based on Islamic teachings.Thus, the partner who commits apostasy by law loses custody of his child, and the wife could not receive the inheritance of the husband,This causes the couple's marital relationship to be damaged (fasakh) and if the convert is the wife, the wife loses her right to care for her child. However, the child is still entitled to inherit through mandatory wills.